When Clientelism Backfires: Vote Buying, Democratic Attitudes, and Electoral Retaliation in Latin America. (September 2022) - Carlin, Ryan E.; Moseley, Mason W.
Attempting to buy votes is, in some cases, inefficient and damaging to a clientelistic party. To explain why, we propose the concept of electoral retaliation: sanctioning clientelistic parties by voting against them or intentionally invalidating the ballot. These forms of negative reciprocity are meant to uphold the democratic norms—equal participation, popular sovereignty, electoral fairness—that vote buying undermines. Electoral retaliation is, we theorize, the domain of "democrats." Thus, we expect voters who highly value democratic norms to be most likely to retaliate against vote-buying parties. We test our theory's observable implications with a research design that pairs case study and subnational evidence from Argentina with cross-national evidence from Latin America. Results are consistent with the notion that when clientelistic parties target democrats, it is likely to backfire on the machine. Our analyses examine multiple indicators of democratic support, explore causal mechanisms, conduct placebo tests, and seek to rule out various forms of selection bias.